A VECTORIZED ALGORITHM FOR MOLECULAR DYNAMICS OF SHORT RANGE INTERACTING PARTICLES - Buchholtz, Volkhard; Pöschel, Thorsten (International Journal of Modern Physics C, 1993)
We report on a lattice based algorithm, completely vectorized for molecular dynamics simulations. Its algorithmic complexity is of the order O(N), where N is the number of particles. The algorithm works very effectively when the particles have short range interaction, but it is applicable to each kind of interaction. The code was tested on a CRAY YMP EL in a simulation of flowing granular material. <br
Keywords: Algorithms; Vectorization; Granular